The Effects of Pasak Bumi (Eurycoma Longifolia Jack) Product on Liver Histology of Wader Pari (Rasbora Lateristriata Bleeker, 1854) - Jihan Restu Buana; Retnoaji, Bambang (Jurnal Biodjati, 2026)
Eurycoma longifolia Jack (commonly known as pasak bumi) is a medicinal plant that contains various bioactive compounds such as eurycomanone, saponins, sterols, and isoprenoids, which are known to exert multiple physiological effects, including on the liver as an organ. This study aimed to examine the effects of pasak bumi root product on liver histology in yellow rasbora (Rasbora lateristriata) as an animal model and to compare the effects between continuous and cyclic (5 days ON, 2 days OFF) administration methods. The experiment lasted 2 weeks, with three treatment groups: control (no extract), continuous administration (P1), and cyclic administration (P2). Observed parameters included liver tissue structure, such as the central vein and hepatocytes arrangement, as well as histological features of hepatocytes. Data were analyzed using one-way ANOVA followed by Duncan’s test. The results showed that pasak bumi administration affected the histological structure of the liver in R. lateristriata, with observable cellular damage including pyknosis, karyorrhexis, and necrosis. Continuous treatment (P2) caused more severe damage than cyclic treatment (P1), which showed tissue structures more similar to those of the control group. Therefore, cyclic administration is considered safer and tends to induce milder liver damage in fish than continuous administration